2017
DOI: 10.1177/0899764017705735
|View full text |Cite|
|
Sign up to set email alerts
|

Nongovernmental Organizations’ Policy Advocacy and Government Responsiveness in China

Abstract: Can the “associational revolution” improve authoritarian government responsiveness? If it can, what kind of nongovernmental organization (NGO) can successfully lobby the government? Based on different theoretical perspectives, I develop three hypotheses: a pluralist hypothesis that focuses on resource exchange between such organizations and the government, a corporatist hypothesis that focuses on government institutional control and policy consultant intention, and a clientelist hypothesis that recognizes the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 39 publications
0
20
0
Order By: Relevance
“…In addition, the MSF model chimes with the identification of some signs of a pluralist tendency in some areas of policy in China. Zhang (2017), for example, noted a growth in civic associations and concluded that China exhibited a hybrid model of state-society relations that had elements 'of both pluralism and state corporatism ' (p. 14). He commented that 'policy-making has become more, albeit selectively, open to social demands and …NGOs with financial, human, and (or) social capital resources can influence governmental policy ' (2017, p. 16).…”
Section: Policy Change and The Multiple Streams Frameworkmentioning
confidence: 99%
“…In addition, the MSF model chimes with the identification of some signs of a pluralist tendency in some areas of policy in China. Zhang (2017), for example, noted a growth in civic associations and concluded that China exhibited a hybrid model of state-society relations that had elements 'of both pluralism and state corporatism ' (p. 14). He commented that 'policy-making has become more, albeit selectively, open to social demands and …NGOs with financial, human, and (or) social capital resources can influence governmental policy ' (2017, p. 16).…”
Section: Policy Change and The Multiple Streams Frameworkmentioning
confidence: 99%
“…Although economic reforms have made Chinese society more decentralized and pluralistic, the state remains the key actor in economic and social ideology. The Chinese political system does not allow open contestation as, for example, the political system in the United States historically has done (C. Zhang, 2017). This reality affects the progress of digital political participation and the choice of response mode.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, even if these non-governmental players served at most as supplementary resources, local government officials remained fearful that the rising profile of these nonstate actors would invigorate civil society and erode the party's rule in the long run (Teets, 2013). As a result, these non-governmental players were strictly, if not unduly, monitored and regulated except when their popularity and credibility could be exploited to help distribute policy directives (Zhang, 2018).…”
Section: Strengths and Weaknesses Of China's Governing Systemmentioning
confidence: 99%